A review of the Integrated Child Development Services’ Supplementary Nutrition Program for Infants and Young Children: Take home ration for children - Vaid, Abhilasha; Avula, Rasmi; George, Nitya Rachel; John, Aparna; Menon, Purnima; Mathews, Pratima (International Food Policy Research Institute, 2018)
We aimed to examine the current policy guidance for ICDS SNP and operationalization of these at the state-level. To do so, we compared India’s SNP guidance for THR with global guidelines for infant and young child feeding (IYCF). Additionally, the current state of the take-home ration supplied for infants and young children across India was reviewed and summarized. Findings on state- and district-specific coverage of services is described elsewhere.